Pembuatan Mesin Pencacah Rumput untuk Meminimalkan Biaya Pakan Ternak dan Meningkatkan Keuntungan pada UMKM Kalijaga Farm - Chandra Syallom, Agung; Satoto , Handy Febri (SURYA TEKNIKA, 2025)
This study reveals the problem of feed waste in UMKM Kalijaga Farm where out of every 30 kg of feed bundles, 10 kg are not eaten. The grass chopper machine was designed using the QFD and Kano methods and the use of a gasoline engine as a driver was chosen because it is efficient and easy to maintain, suitable for remote locations without electricity, so it supports operations and increases farmer profits. The designed machine measures 80×50×100 cm, uses SKD-11 steel blades and thick iron plates for durability. Kano classification produces 2 must be attributes, 4 indifferent, 1 attractive, and 1 dimensional. For mobility, the machine is equipped with iron pipe handles on both sides and two bottom wheels. The HPP analysis shows a decrease in operational costs from IDR 115,100,000 to IDR 103,600,000, increasing the profit of UMKM Kalijaga Farm from IDR 29,400,000 to IDR 42,000,000.